Pharmacokinetics of intramuscularly administered aminosidine in healthy subjects. - Kanyok, T P (1997)
Aminosidine is an older, broad-spectrum aminoglycoside antibiotic that has been shown to be effective in in vitro and animal models against multiple-drug-resistant tuberculosis and the Mycobacterium avium complex. The objective of this randomized, parallel trial was to characterize the single-dose pharmacokinetics of aminosidine sulfate in healthy subjects (eight males, eight females). Sixteen adults (mean [+/- standard deviation] age, 27.6 +/- 5.6 years) were randomly allocated to receive a single, intramuscular aminosidine sulfate injection at a dose of 12 or 15 mg/kg of body weight. Serial plasma and urine samples were collected over a 24-h period and used to determine aminosidine concentrations by high-performance liquid chromatographic assay. A one-compartment model with first-order input, first-order output, and a lag time (Tlag) and with a weighting factor of 1/y2 best described the data. Compartmental and noncompartmental pharmacokinetic parameters were estimated with the microcomputer program WinNonlin. One subject was not included (15-mg/kg group) because of the lack of sampling time data. On average, subjects attained peak concentrations of 22.4 +/- 3.2 microg/ml at 1.34 +/- 0.45 h. All subjects had plasma aminosidine concentrations below 2 microg/ml at 12 h, and all but two subjects (one in each dosing group) had undetectable plasma aminosidine concentrations at 24 h. The dose-adjusted area under the concentration-time curve from 0 h to infinity of aminosidine was identical for the 12- and 15-mg/kg groups (9.29 +/- 1.5 versus 9.29 +/- 2.2 microg x h/ml per mg/kg; P = 0.998). Similarly, no significant differences (P > 0.05) were observed between dosing groups for peak aminosidine concentration in plasma, time to peak aminosidine concentration in plasma, Tlag, apparent clearance, renal clearance, elimination rate constant, and elimination half-life. A significant difference was observed for the volume of distribution (0.35 versus 0.41 liters/kg; P = 0.037) between the 12 and 15 mg/kg dosing groups. Now that comparable pharmacokinetic profiles between dosing groups have been demonstrated, therapeutic equivalency testing via in vitro pharmacokinetic and pharmacodynamic modelling and randomized clinical trials in humans should be conducted.